PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA USAHA KONVEKSI ADIGUNA KOTA BENGKULU - Azis Saefulloh; Sri Ekowati (UM. Bengkulu, 2021)
This study aimed to find outthe effect of training on employee performance with motivation as an Intervening variable in the Adiguna Convection Business at Bengkulu City. There were several factors that would be discussed in this study, including training and motivation as Intervening variables. The object in this study were 40 employees at the Adiguna Convection Business in Bengkulu City. In this study, the researcher employed data collection methods through conducting observation, interviews and distributing questionnaires. There were several data analysis techniques employed in this study, including using instrument tests, classical assumption tests, analysis of respondent responses, simple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the Training variable (X) has a positive and significant effect on Employee Performance (Y) at the Adiguna Convection Business in Bengkulu City.Then, the motivation variable (Z) mediates training positively and significantly on employee performance (Y) at the Adiguna Convection Business in Bengkulu City. Moreover, from the results of the simple linear regression test, the regression equation is gained as follows: The first equation, Z = 3.530 + 1.053 (X). The second equation Y = 0.749 + 1.095 (X). Third equation Y = 2.067 + 1.027 (Z)Â Keywords: Training, Motivation And Employee Performance